2016
DOI: 10.11138/ccmbm/2016.13.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Atypical periprosthetic acetabular fracture in long-term alendronate therapy

Abstract: SummaryBisphosphonates have been commonly used in the treatment of osteoporosis, demonstrating its efficacy in fracture risk reduction. However, even if are generally safe and well tolerated, concerns have emerged about atypical fractures related to its prolonged use. Although atypical femoral fracture are more common, case reports demonstrated that even other skeletal areas can be involved by unusual pattern of fracture. We report a atypical acetabular periprosthetic fracture in a 83-year-old female patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Periprosthetic joint infections represent one of the most common complication following joint arthroplasty, both after primary or revision surgery [18][19][20][21]. However tubercular PJI is a rare clinical condition in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Periprosthetic joint infections represent one of the most common complication following joint arthroplasty, both after primary or revision surgery [18][19][20][21]. However tubercular PJI is a rare clinical condition in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Classified as a spontaneous fragility fracture with substantial bone stock loss [18], the patient therefore underwent acetabular revision surgery without fracture fixation, as proposed by Simon et al [19]. This solution has been reported by other authors with good results in terms of fracture healing and functional results [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Results from experimental studies on ovariectomized rats suggested the tibia fractures treated with strontium ranelate heal faster, with abundant callus and with higher BMD. Regarding the clinical use of strontium ranelate for fracture healing, the evidence is limited to clinical cases that suggest a potential benefit in complicated long bones fractures, atypical fractures and periprosthetic femoral fractures [11,[88][89][90].…”
Section: Strontium Ranelatementioning
confidence: 99%
“…Pharmacological interventions that could modulate the healing process positively have been recently merged to the treatment algorithm, where systemic anti-osteoporosis drugs are considered the additional contributing factor [8]. The role of systemic drug therapies in long bones fracture healing remains limited, although the use several anabolic agents has reported positive results in selected shaft fractures types, such as atypical femoral fractures, periprosthetic femoral fractures and recalcitrant non-unions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%